Spinal Fluid Lactate Dehydrogenase Level Differentiates between Structural and Metabolic Etiologies of Altered Mental Status in Children - KHOSROSHAHI, Nahid; ALIZADEH, Parastoo; KHOSRAVI, Mehdi; SALAMATI, Peyman; KAMRANI*, Kamyar (Iranian Journal of Child Neurology, 2015)
How to Cite This Article: Khosroshahi N, Alizadeh P, Khosravi M, Salamati P, Kamrani K. Spinal Fluid Lactate Dehydrogenase Level Differentiates between Structural and Metabolic Etiologies of Altered Mental Status in Children. Iran J Child Neurol. 2015 Winter;9(1):31-36. Abstract Objective Altered mental status is a common cause of intensive care unit admission in children. Differentiating structural causes of altered mental status from metabolic etiologies is of utmost importance in diagnostic approach and management of the patients. Among many biomarkers proposed to help stratifying patients with altered mental status, spinal fluid lactate dehydrogenase appears to be the most promising biomarker to predict cellular necrosis. Materials & Methods In this cross sectional study we measured spinal fluid level of lactate dehydrogenase in children 2 months to 12 years of age admitted to a single center intensive care unit over one year. Spinal fluid level of lactate dehydrogenase in 40 pediatric cases of febrile seizure was also determined as the control group. Results The study group included 35 boys (58.3%) and 25 girls (41.7%). Their mean age was 2.7+/-3 years and their mean spinal fluid lactate dehydrogenase level was 613.8+/-190.4 units/liter. The control group included 24 boys (55.8%) and 19 girls (44.2%). Their mean age was 1.3+/-1.2 years and their mean spinal fluid lactate dehydrogenase level was 18.9+/-7.5 units/liter. The mean spinal fluid lactate dehydrogenase level in children with abnormal head CT scan was 246.3+/-351.5 units/liter compared to 164.5+/-705.7 in those with normal CT scan of the head (p=0.001). Conclusion Spinal fluid lactate dehydrogenase level is useful in differentiating structural and metabolic causes of altered mental status in children. References Fesk SK. Coma and confusional states: emergency diagnosis and management. Neurol Clin 1998; 16: 237- 56. Cucchiara BL, Kanser SE, Wolk DA, et al. Early impairment in consciousness Predicts mortality after hemispheric ischemic stroke. Crit care med 2004; 32: 241-5. Teasdale G, Jennett B. Assessment of coma and impaired consciousness: a practical scale. Lancet 1974; 2: 81-4. Wityk RJ, Stern BJ. Ischemic stroke: today and tomorrow. Crit care med 1994; 22: 1278-93. Vázquez Jorge Alejandro, Adducci Maria del Carmen, Monzón Daniel Godoy, Iserson Kenneth V. Lactic dehyrogenase in cerebrospinal fluid may differentiate between structural and non-strucfiular central nervous system lesion in patient with diminished levels of consciousness. The Journal of Emergency Medicine2009; 37(1): 93–97. Kärkelä J, Pasanen M, Kaukinen S, Mörsky P, Harmoinen A. Evaluation of hypoxic brain injury with spinal fluid enzymes, lactate, and pyruvate. Crit Care Med. 1992 Mar; 20(3):378-86. 2007: pp. 835. ISBN 0-7817-7087-4. DV Kamat, BP Chakravorty. Comparative values of CSF-LDH isoenzymes in neurological disorders. Indian Journal of Medical Sciences 1999; 53 (1): 1-6. Pollak AN, Gupton CL. Emergency Care and Transportation of the Sick and Injured. Boston: Jones and Bartlett 2002: pp. 140. ISBN 0-7637-1666-9. Nayak BS, Bhat R. Cerebrospinal fluid lactate dehydrogenase and glutamine in meningitis. Indian J Physiol Pharmacol. 2005 Jan; 49(1):108-10. A Twijnstra, A P van Zanten, A A Hart, et al. al. Serial lumbar and ventricle cerebrospinal fluid lactate dehydrogenase activities in patients with leptomeningeal metastases from solid and haematological tumours. J Neurol Neurosurg Psychiatry 1987 50: 313-320. Nussinovitch M, Finkelstein Y, Politi K, Harel D, Klinger G, Razon Y, Nussinovitch U, Nussinovitch N. Cerebrospinal fluid lactate dehydrogenase isoenzymes in children with bacterial and aseptic meningitis. Translational Research 2009. 154 (4): 214-218. Feldman William E. Cerebrospinal Fluid Lactic Acid Dehydrogenase Activity. Levels in Untreated and Partially Antibiotic-Treated Meningitis. Am J Dis Child. 1975; 129(1): 77-80. Lutsar I, Haldre S, Topman M, Talvik T. Enzymatic changes in the cerebrospinal fluid in patients with infections ofthe central nervous system. Acta Paediatr 1994; 83(11):1146-1150. Kepa L, Oczko-Grzesik B, Błedowski D. Evaluation of cerebrospinal fluid and plasma lactate dehydrogenase activity in patients with purulent, bacterial meningoencephalitis. Przegl Epidemiol. 2006; 60(2):291-8. Ruzak-Skocir B, Trbojevic-Cepe M. Study of serum and cerebrospinal fluid enzymes in diagnosis and differential diagnosis of cerebrovascular diseases. Neurologija. 1990; 39(4):239-50. Nand N, Sharma M, Saini DS. Evaluation of lactic dehydrogenase in cases of meningitis. Indian J Med Sci. 1993; 47(4): 96-100. Neches William, Platt Martin. Cerebrospinal Fluid LDH in 287 Children, Including 53 Cases of Meningitis of Bacterial and non-Bacterial Etiology. Pediatrics 1968; 41:1097-1103. Engelke S; Bridgers S, Saldanha R, Trought W. Cerebrospinal Fluid Lactate Dehydrogenase in Neonatal Intracranial Hemorrhage. American Journal of the Medical Sciences 1986; 291 (6): 391-395. Parakh N, Gupta HL, Jain A. Evaluation of enzymes in serum and cerebrospinal fluid in cases of stroke. Neurology India 2002; 50 (4): 518-9. Lampl Y, Paniri Y, Eshel Y, Sarova-Pinhas I. Cerebrospinal fluid lactate dehydrogenase levels in early stroke and transient ischemic attacks. Stroke 1990; 21: 854-857. Hall Robert T., Kulkarni Prakash B., Sheehan Michael B., Rhodes Philip G. Cerebrospinal Fluid Lactate Dehydrogenase in Infants with Perinatal Asphyxia. Developmental Medicine & Child Neurology 1980. 22 (3): 300-307. Nussinovitch M, Volovitz B, Finkelstein Y, Amir J, Harel D. Lactic dehydrogenase isoenzymes in cerebrospinal fluid associated with hydrocephalus. Acta Paediatr 2001; 90: 972-974.